Infective endocarditis due to Atopobium vaginae: a rare association between genital infection and endocarditis of the tricuspid valve. (1st September 2018) - Mansell, Josephine; Gourtsoyannis, Yannis; Draz, Nehal; Buchanan, Ruaridh
Abstract : Atopobium vaginae is an anaerobic gram-positive organism associated with genitourinary infections. Bacteraemia is rare, with only two cases reported in the literature. This case describes an 18-year-old type 1 diabetic, presenting with sepsis and haemoptysis, on a background of poor dental hygiene and recurrent hospital admissions. Blood cultures grew A. vaginae and echocardiogram revealed a large tricuspid valve lesion. Despite medical therapy, symptoms of pulmonary emboli continued and she therefore underwent surgical resection of the lesion. Histopathological findings were of a vegetation; culture of the lesion was negative but 16S ribosomal PCR was positive, detecting 16S rRNA of A. vaginae . The patient was treated with 4 weeks of vancomycin and made a good recovery. To our knowledge, this represents the first report of infective endocarditis due to this organism. We also provide a review of the literature, including comparing published drug susceptibility data with consensus breakpoints for antimicrobial agents.